Effectiveness of Law Enforcement in Corruption Crime Investigations (Case Study of the Ternate Police Resort, North Maluku) - Naufal Fajar Zanira; Andri Winjaya Laksana (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The investigation of corruption cases is a crucial stage in law enforcement because it determines the quality of evidence and the continuation of the judicial process. At the Ternate Resort Police, efforts to combat corruption face various challenges, ranging from case complexity to limited resources. This study aims to evaluate the effectiveness of law enforcement in the investigation of corruption crimes at the Ternate Resort Police and to identify the obstacles affecting investigator performance, thereby formulating strategies to enhance accountability and professionalism in the investigation process. This research employs an empirical legal method with a qualitative approach. Data were obtained through literature review, examination of official investigative documents, in-depth interviews with investigators, and direct observation of ongoing case handling. The analysis was conducted descriptively and analytically by referring to Lawrence M. Friedman’s legal system theory and Soerjono Soekanto’s factors of legal effectiveness, enabling a comprehensive assessment of the interplay among legal substance, legal structure, and legal culture in the practice of corruption investigations. The findings show that corruption investigations at the Ternate Resort Police generally adhere to procedural requirements, and several cases have successfully reached the P21 stage. However, law enforcement effectiveness is not yet optimal due to limited personnel and investigator competence, inadequate investigative facilities, the complexity of document-based evidence, and coordination challenges among institutions. This study highlights the need for strengthening investigator capacity, improving investigative infrastructure, and developing more robust inter-agency coordination mechanisms as strategic measures to enhance the effectiveness of corruption case investigations in the region.